(untitled) (American Journal of Islam and Society, 2020)
The Kaʿba has central role in Islamic culture. It orients Muslims both physically and perceptually in their daily lives and worship. Recognising its obscurity in extant scholarship on Islamic art and architecture, Simon O’Meara seeks to understand how the Kaʿba works in the Islamic world. Inspired by Erwin Panofsky’s iconological method, he looks to the indigenous documents of the Islamic tradition, including the textual, visual and architectural. He extracts six different orientations of the Kaʿba (as qibla, navel, substructure, beloved, holder, and dwelling), with one chapter devoted to each. The first of its kind, O’Meara’s monograph is a highly original study which has paved the path for not only for future studies of the Kaʿba but also for all studies of Islamic art and architecture that are grounded in Islamic culture and tradition. Download